2001
DOI: 10.1177/00131640121971563
|View full text |Cite
|
Sign up to set email alerts
|

A Study Strategies Self-Efficacy Instrument for Use with Community College Students

Abstract: Theories of self-efficacy and self-regulation were used to examine scores from an instrument that measures self-efficacy for using self-regulatory study strategies. The authors investigated the dimensionality of responses to the Study Skills Self-Efficacy Scale using exploratory factor analysis and Rasch measurement. They also investigated the utility of the Rasch measures in differentiating between groups of students who report being academically successful or at risk. The participants were 550 social science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Trice reported acceptable test-retest reliability for a five week interval at .92. Participants also completed the 32-item Study Skills Self-Efficacy Scale (Silver, Smith, & Greene, 2001), which has students rate how accurately each statement describes their behavior along a 6-point Likert scale (1 = strongly agree, 6 = strongly disagree). This scale measures student selfefficacy, or confidence, in study strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Trice reported acceptable test-retest reliability for a five week interval at .92. Participants also completed the 32-item Study Skills Self-Efficacy Scale (Silver, Smith, & Greene, 2001), which has students rate how accurately each statement describes their behavior along a 6-point Likert scale (1 = strongly agree, 6 = strongly disagree). This scale measures student selfefficacy, or confidence, in study strategies.…”
Section: Methodsmentioning
confidence: 99%
“…To create the LSSS, Ruban (1999) drew from the 47-item Study Skills Self Efficacy Scale (SSSE) of Ramirez and Owen (1991) and from Zimmerman's (1989) publications on selfregulated learning. Alpha reliabilities for each of the 5 factors on the SSSE, which were incorporatedinthe LSSS andsubsequently inthe AUSSLS, ranged from .78 to .91 (Ruban, McCoach, McGuire, & Reis, 2003;Silver, Smith, & Greene, 2001). …”
Section: Instrumentmentioning
confidence: 99%
“…Self-efficacy represents the student's belief that he or she can successfully perform a task (Bandura, 1997;Pajares, 1996;Schunk, 1991). Researchers have found that students with high self-efficacy are more likely to make use of deep cognitive strategies and to engage in self-regulation than students with low self-efficacy (Li & Cheung, 2001;Meece, Blumenfeld, & Hoyle, 1988;Miller, Behrens, & Greene, 1993;Pintrich, 1989Pintrich, , 1999Pintrich & De Groot, 1990;Pintrich & Garcia, 1991;Pintrich & Schrauben, 1992;Pokay & Blumenfeld, 1990;Schunk & Ertmer, 2000;Silver, Smith, & Greene, 2001;Wolters & Pintrich, 1998;Zimmerman, 2000Zimmerman, , 2002Zimmerman & Martinez-Pons, 1992).…”
Section: Students' Academic Achievementmentioning
confidence: 99%